Temporalis muscle flap in craniofacial reconstruction: anatomy, techniques, outcomes, and innovations - Landfald, Ingrid C.; Vazquez, Teresa; Okoń, Adrian; Olewnik, Łukasz (Frontiers in Surgery, 2025)
BackgroundThe temporalis muscle flap (TMF) remains an essential reconstructive option in contemporary craniofacial reconstructive surgery (CRS) owing to its reliable vascularity, anatomical proximity to common defect areas, and substantial soft tissue volume. Despite extensive historical use, evolving surgical approaches and novel adjunctive technologies necessitate an updated comprehensive review to guide current clinical practice.ObjectiveThis review critically examines the TMF regarding its anatomical considerations, surgical innovations, clinical outcomes, and functional restoration capacities. Additional objectives include a detailed assessment of clinical complications, identification of existing gaps in knowledge, and evidence-based comparisons with alternative reconstructive techniques.MethodsAn extensive literature review was conducted utilizing current high-quality publications, including systematic reviews, clinical series, cadaveric anatomical studies, and reports detailing innovative techniques from major surgical journals. Specific emphasis was placed on the latest minimally invasive, endoscopic, and robotic-assisted approaches, alongside novel tissue engineering methodologies and virtual surgical planning (VSP). Clinical outcomes, complication rates, patient satisfaction levels, and comparative analyses with alternative reconstructive flaps, including free tissue transfers and other regional flaps, were rigorously assessed.ConclusionTMF remains a versatile, robust, and highly reliable reconstructive option within modern craniofacial surgery. Anatomical knowledge, meticulous surgical technique, and incorporation of emerging adjunctive technologies significantly enhance outcomes while minimizing morbidity. Continued research into minimally invasive techniques, regenerative medicine, functional restoration through advanced nerve transfers, and secondary refinement procedures is essential to further improve clinical efficacy, patient satisfaction, and overall quality of life.